2018
DOI: 10.1016/j.jpain.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes and Opioid Use by Outpatient Cancer Patients

Abstract: This report describes the results of the analyses of PROs and patient-related electronic health record data collected under standard of care from cancer patients at outpatient pain management clinics of Anesthesiology and Palliative Care at the Memorial Sloan Kettering Cancer Center. Consideration of sex and age as predictors of opioid use is critical in attempting to understand PROs and their relationship to pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 48 publications
6
24
0
Order By: Relevance
“… 1 Patients with cancer often have more than 1 pain location. 2 , 3 , 4 Even when the index pain from the irradiated tumors is controlled, new pain from tumors outside of the irradiated area may have a negative effect in terms of the interference of pain in the patient's life and may negatively affect quality of life. 5 To our knowledge there are no data regarding the frequency or causes of nonindex pain in patients treated with palliative RT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Patients with cancer often have more than 1 pain location. 2 , 3 , 4 Even when the index pain from the irradiated tumors is controlled, new pain from tumors outside of the irradiated area may have a negative effect in terms of the interference of pain in the patient's life and may negatively affect quality of life. 5 To our knowledge there are no data regarding the frequency or causes of nonindex pain in patients treated with palliative RT.…”
Section: Introductionmentioning
confidence: 99%
“…Pain response after radiation therapy (RT) is assessed using the intensity of the index pain (pain caused by the irradiated tumor) 1 . Patients with cancer often have more than 1 pain location 2, 3, 4. Even when the index pain from the irradiated tumors is controlled, new pain from tumors outside of the irradiated area may have a negative effect in terms of the interference of pain in the patient's life and may negatively affect quality of life 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The results from that study indicate that 26.3% who reported severe pain received opioids during the 30-day pre-period, which matches the 27.0% reported in this study. Several other smaller studies that have assessed pain symptoms and medication management find higher opioid use rates, but these tend to be clinical cohorts of oncology patients undergoing active treatment or surveillance [12,21], which are more homogeneous than our sample. While numerous other studies address pain medication use overall [22][23][24][25][26][27] or either for adults with [28][29][30][31][32][33][34][35] or without cancer [36,37], few compare medication patterns across these groups within a single population setting [8,9]; incorporation of patient-reported pain information is rare.…”
Section: Discussion/conclusionmentioning
confidence: 90%
“…Opioids are the most commonly prescribed medications used to treat pain, prescribed for as many as two-thirds of those reporting severe pain [7]. Recent studies have reported higher opioid use rates for adults with, compared with without cancer [8][9][10][11], but few population-based studies have examined associations between pain medication use and pain severity [7,12] and whether it differs for older adults with and without cancer.…”
Section: Background/introductionmentioning
confidence: 99%
“…Improved night sleep in terms of longer duration and less frequent awakenings, mainly due to the absence of leg cramps and spasms, after ITB treatment was achieved in all patients. BPI is an instrument that was primarily used to assess cancer-related pain, but its use has also been extended to chronic nonmalignant pain with good validity [23, 29]. An improved body posture in patients that had a fixed position before the ITB pump implantation, followed by a better sitting posture in the wheelchair due to the lack of spasticity, was documented in all patients.…”
Section: Discussionmentioning
confidence: 99%